Comparative Evaluation of Existing and Rationally Designed Novel Antimicrobial Peptides for Treatment of Skin and Soft Tissue Infections - Anna Ramata-Stunda; Martins Boroduskis; Elza Kaktina; Liene Patetko; Uldis Kalnenieks; Zane Lasa; Marta Rubina; Inese Strazdina; Gints Kalnins; Reinis Rutkis (MDPI AG, 2023)
Skin and soft tissue infections (SSTIs) and acne are among the most common skin conditions in primary care. SSTIs caused by ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter sp.) can range in severity, and treating them is becoming increasingly challenging due to the growing number of antibiotic-resistant pathogens. There is also a rise in antibiotic-resistant strains of Cutibacterium acne, which plays a role in the development of acne. Antimicrobial peptides (AMPs) are considered to be a promising solution to the challenges posed by antibiotic resistance. In this study, six new AMPs were rationally designed and compared to five existing peptides. The MIC values against E. coli, P. aeruginosa, K. pneumoniae, E. faecium, S. aureus, and C. acnes were determined, and the peptides were evaluated for cytotoxicity using Balb/c 3T3 cells and dermal fibroblasts, as well as for hemolytic activity. The interaction with bacterial membranes and the effect on TNF-α and IL-10 secretion were also evaluated for selected peptides. Of the tested peptides, RP556 showed high broad-spectrum antibacterial activity without inducing cytotoxicity or hemolysis, and it stimulated the production of IL-10 in LPS-stimulated peripheral blood mononuclear cells. Four of the novel AMPs showed pronounced specificity against C. acnes, with MIC values (0.3-0.5 μg/mL) below the concentrations that were cytotoxic or hemolytic.